Study on Etiological Evaluation of Convulsions in Children from 1 Month to 14 Years of Age - Ramesh, Shanthi; Sundari, S. (New Frontiers in Medicine and Medical Research Vol. 10, 2021)
Background: Seizures are a prevalent condition seen in Pediatric emergency departments all around the world. Objective: The aim of this study was to investigate the etiology of convulsions in children aged 1 month to 14 years. Methods: Between June 2014 and May 2015, 120 children admitted to a tertiary care hospital's paediatric department with convulsions were studied in this cross-sectional study.All of the children had a complete blood count, blood sugar, serum calcium, magnesium, and electrolytes checked. Depending on the clinical circumstances, Mantoux, chest X-ray, liver biopsy, Electroencephalography, lumbar puncture and cerebrospinal fluid analysis, ultrasonography cranium, computed tomography brain, or magnetic resonance imaging brain was performed. Results: We discovered that 46.7% of the children had febrile seizures, 19.2% had a seizure disorder, 15% had cerebral palsy, 5.8% had viral encephalitis, 3.3% had pyogenic meningitis, 1.7% had neurocysticercosis, 0.8% had metabolic disorders, and 0.8% had a traumatic brain injury, with the cause of seizures unknown in 6.6% of the children. Conclusion: Seizures in children require a thorough examination to determine the underlying pathology that is causing the seizures.